Analisis Ekonomi Wilayah pada Kabupaten/Kota Provinsi Nusa Tenggara Timur - Umbu Nday, Samuel (REKSABUMI, 2025)
Economy is one of the indicators that signifies the development of a district/city. Regional economic analysis at the district/city level in NTT province differs in terms of planning and administrative scope. Income becomes the focus of research, and the results will serve as a guide for strategic development. The society remains a focus in developing a market that can contribute to their income. The methods used are quantitative and qualitative, with specific analysis results and findings that help identify the factors influencing market development. Various changes in the analysis findings can serve as measures of economic growth. Economic development in the NTT region does not only on the districts/cities within it. But also show interest to national economic development. Therefore, the expected analysis results are not limited to the provincial scope but are relevant to national data. Through cluster analysis, location quotient, and multiplier effect on 22 regencies/cities, we will examine groups, economic bases, and potential for economic development. The results of the regional economic analysis that influences the direction of economic development in districts/cities in East Nusa Tenggara will help provide an overview related to economic planning. Emphasis on enhancing economic growth for the economy and its potential sectors at the district/city level as well as in broader regions is needed through the roles of various stakeholders.